Insertionally polymorphic sites of human endogenous retrovirus-K (HML-2) with long target site duplications - Kahyo, Tomoaki (BMC Genomics, 2017)
BACKGROUND: Human endogenous retroviruses (HERVs) belong to the LTR-retrotransposon family, where the complete HERV sequence contains two long terminal repeats (LTRs) located at each end. Intact LTRs possess highly conserved transcriptional promoter and enhancer sequences, so analyses of HERV insertional polymorphisms are expected to provide greater insights into human genomic variation compared with the conventional analysis of single nucleotide variations. High-throughput sequencing technology is developing but genome-wide investigations of HERVs are methodically challenging, and thus a comprehensive understanding of HERV insertional polymorphisms and target site duplications (TSDs) remains elusive. RESULTS: We identified five human-specific insertionally polymorphic sites in HERVK (HML-2), one of the HERV subgroups, by extracting HML-2-deleted sequences from the genomic structural variation database, which we successfully characterized and then updated the existing catalogue of HML-2 insertional polymorphisms. The insertionally polymorphic states were confirmed in a small Japanese population by genomic PCR analysis for four of the five sites identified. Sequencing of the preintegration sites clearly showed that the HML-2 site located at 7p21.2 had 250-base pair (bp) TSDs, which is one of the longest TSDs in HML-2. In addition to these five sites, another insertionally polymorphic site for a non-human-specific HML-2 site was also identified at 6p25.2, which was flanked by 111-bp TSDs and the corresponding ERV locus was also annotated in the genome of non-human primates. CONCLUSIONS: Our analysis demonstrated the existence of HERV insertions flanked by unconventionally long TSDs, including those with lengths as high as 250 bp. This suggests that the length range of retroviral TSDs is larger than considered previously, which might help to understand how retroviral integration occurs in the host genome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-3872-6) contains supplementary material, which is available to authorized users.